Electrical design of solar-powered recreational boat in Malaysia - Umi Shahira; Islam, Syed Zahurul; Omar, Rosli; Othman, Mohammad Lutfi; Said, Said Zakaria; Uddin, Jasim (IEEE, 2022)
This paper presents the electrical design of a solar powered electric boat for recreational activities in Malaysia. Increase in fossil fuel prices and river pollution cases in Malaysia lead this research to implement electric boat powered by solar energy and help reducing oil-spill and river water pollution. The main objective is to design a zero-emission recreational boat which is fully powered by battery integrated Photovoltaic (PV) panel. In the proposed design, the specifications of flexible PV panel, Lithium Iron Phosphate (LiFePO4 or LFP) battery, Maximum Power Point Tracking Technique (MPPT) charge controller, and Brushless DC (BLDC) motor are considered based on the boat size, weight, and capacity. The design is modelled in Simulink for performance analysis of the PV, battery, and the motor to verify its feasibility in this application. In addition, we modelled BLDC motor and propeller power to ensure that the motor always produces more power than the power required by the propeller. Then a small scale prototype is implemented followed by the normalized value of design parameters and tested for 4 h in UTHM, Johor, Malaysia. Parameters, such as solar irradiance, motor speed, and voltages at battery, PV, motor terminals are collected at frequency of 1 data at every 10 min. The simulation results in terms of battery charging voltage and motor speed are validated by the experimental data. Both analyses indicate a stable charging voltage at battery terminal which drives the BLDC motor to run continuously at a steady- state speed of 2500 rpm with no-load condition test.